Principal Leadership in the Development of Teacher Pedagogical Competence - Rahmadi, Bobby; Arafat, Yasir; Setiawan, Andi Arif (Journal of Social Work and Science Education, 2021)
This study described the principal's leadership in guiding teacher pedagogic competence at SMP Negeri 1 Ogan Komering Ulu. This study used a qualitative method where observation, interviews, and documentation used as instruments. The research subjects were principals, teachers and staff. The results of this study indicate that the principal has two leadership styles in empowering and mobilizing teachers and staff. The two styles are charismatic and democratic leadership style. The principal used four models of pedagogical competency development for teachers were supervision, workshops, regular meetings, and the principal directs teachers to participate in educational trainings and seminars. The obstacles were the lack of teacher preparation in making learning tools such as lesson plans and syllabus, the schedule of the principal's activities impromptu so that the implementation of supervision, meetings, or workshops is delayed. There are some teachers who cannot attend meetings or workshops.